Analisis Proses Produksi Program Citraloka di DAAI TV Pada Episode "Markisa Yang Melegenda" - Andini Nur Bahri; Ayu Sawitri; Fariz Rizwan Siregar; Khafita Aini; Ramadhani Nanda Amelia; Syahrul Afriansyah (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
This program is one of the interesting programs on DAAI TV Medan. And it is not surprising that this program has received various awards from the North Sumatra KPID. So that researchers want to examine the production process of the Sumatra Frame program which has been trying to improve the corporate image of DAAI TV Medan. The purpose and benefits of this research are to find out the production process of the Citraloka program in building the image of DAAI TV Medan and I hope this research can be useful for readers. The research used is a descriptive qualitative approach. The theoretical description in this study uses mass communication, communication processes, agenda setting theory, and program production processes. The results of this study are the production process carried out by DAAI TV Medan in making news regularly from pre-production, production and post-production. The pre-production stage here begins with a projection meeting by gathering ideas according to the vision and mission, and related to inspirational values. Production activities, namely a reporter doing live coverage of the field. Then in post-production the process of editing and merging the coverage results into one news package. The Citraloka program has an inspiring value as a means of education for the community. Its consistency as a broadcasting media broadcasting useful news is quite good. DAAI TV Medan has carried out its social responsibility so that it has a good image in the community, and does not look at the ratings that have been achieved, but looks at how useful the broadcasts are.